2007
DOI: 10.1039/b607983k
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular reactions of electron-rich heterocycles with copper and rhodium carbenoids

Abstract: This tutorial review describes the reactions of the electron-rich heterocycles pyrrole, furan, indole and benzofuran with copper and rhodium carbenoids. Two main reaction pathways are possible, involving either a concerted non-synchronous cyclopropanation or zwitterionic intermediates. A diverse range of products are possible and the outcome is very dependent on the structure of the heterocycle and the carbenoid. To emphasize this point the carbenoids are considered in terms of three classes: acceptor, accepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
97
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(104 citation statements)
references
References 33 publications
2
97
0
1
Order By: Relevance
“…Treatment of 7e with TMSOTf (2 equiv) and 2,2'-bipyridyl (3 equiv) in CH 2 Cl 2 at 0 °C led to the exclusive cleavage of the methyl ether linkage of Table 3 Enantioselective C-H functionalization of indoles 5f-k with 2,4-dimethyl-3-pentyl -diazopropionate 6a catalyzed by Rh2(S-PTTEA)4 1f Using the present catalytic protocol, we conducted an asymmetric synthesis of (+)--methyl-3-indolylacetic acid 11, 31 a phytohormone of the auxin class 32 and a constituent of a potent plant-growth inhibitor acremoauxin A 12 (Scheme 3). 33,34 Alcohol ent-10 was prepared using Rh 2 (R-PTTEA) 4 oxidation of a primary alcohol tethered to an unmasked indole substituent to carboxylic acid in the total synthesis of (+)-asperazine. 35 Following this precedent, oxidation of alcohol ent-10 under standard Parikh-Doering conditions 36 38 This is the first catalytic asymmetric synthesis of the (+)--methyl-3-indolylacetic acid fragment of 12.…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of 7e with TMSOTf (2 equiv) and 2,2'-bipyridyl (3 equiv) in CH 2 Cl 2 at 0 °C led to the exclusive cleavage of the methyl ether linkage of Table 3 Enantioselective C-H functionalization of indoles 5f-k with 2,4-dimethyl-3-pentyl -diazopropionate 6a catalyzed by Rh2(S-PTTEA)4 1f Using the present catalytic protocol, we conducted an asymmetric synthesis of (+)--methyl-3-indolylacetic acid 11, 31 a phytohormone of the auxin class 32 and a constituent of a potent plant-growth inhibitor acremoauxin A 12 (Scheme 3). 33,34 Alcohol ent-10 was prepared using Rh 2 (R-PTTEA) 4 oxidation of a primary alcohol tethered to an unmasked indole substituent to carboxylic acid in the total synthesis of (+)-asperazine. 35 Following this precedent, oxidation of alcohol ent-10 under standard Parikh-Doering conditions 36 38 This is the first catalytic asymmetric synthesis of the (+)--methyl-3-indolylacetic acid fragment of 12.…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%
“…3 In this context, C-H functionalization of indoles with metal carbenes generated from -diazocarbonyl compounds under catalysis by metal complexes is a potentially powerful means for installing functionalized alkyl groups on the pyrrole portion of the indole ring system. 4,5 Since publication of the seminal work of Davies and Lian on catalysis by Rh 2 (S-DOSP) 4 4 6 (Figure 1), 7 the development of an enantioselective version of this catalytic process has been a challenging objective. Very recently, Fox and co-workers made a major breakthrough in this field when they demonstrated that enantioselective C-H functionalization of indoles with ethyl -alkyl--diazoacetates under catalysis by Rh 2 (S-NTTL) 4 3 [8][9][10] provides -alkyl-substituted 3-indolylacetates in high yields and enantioselectivities (82-96% yields, 79-99% ee, Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiral dirhodium(II) complexes are currently renowned as catalysts that can effectively drive a broad spectrum of reactions with superior levels of chemo-, regio-and stereo-selectivity [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Their remarkable selectivity has reached a stage where they can function as a powerful tool in building up value added molecules with complex structures [7,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Chiral dirhodium(II) paddlewheel complexes are among the most attractive catalysts that found a widespread application in the fields of metal-nitrene and metal-carbene transformations [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. This immense interest originates from their exceptional ability to effectively catalyze a broad spectrum of reactions with high levels of chemo-, regio-and stereo-selectivity.…”
Section: Introductionmentioning
confidence: 99%